The Method of Selecting Boiler Houses under Technical Re-Equipment in a Mini-CHP - Myshkina L.S.; Frolova Y.A.; Ivanova E.M. (Problems of the Regional Energetics, 2023)
The development of the energy sector is aimed at improving the energy efficiency of heat and electricity. One way is to use cogeneration technologies. A large number of boiler houses created the preconditions for the creation of a mini-CHPP through their technical re-equipment. The purpose of the work is to develop a methodology for selecting and ranking boiler houses for transformation into a mini-CHPP. To achieve the goal, the following tasks were solved: the ef-fects of the formation of a mini-CHP in the energy district were revealed; a system of criteria has been developed that determines the feasibility of transforming a boiler house; a ranking co-efficient was proposed that reflects the potential for improving efficiency; the methodology was tested. The difference of the work is the complexity of the methodology, which takes into ac-count both the advantages of cogeneration technologies and energy balances, as well as individ-ual features of each boiler house. Multi-criteria selection of boiler houses is based on the pur-pose, fuel used, heat output and functions in heat supply systems. The technical condition, pro-spective balances of production and consumption of electricity in the energy district of a mini-CHPP are taken into account. The significance of the results lies in the fact that the proposed methodology makes it possible to increase the validity of decisions when transforming a boiler house into a mini-CHPP. The use of the selection results will lead to an increase in the economic efficiency of the heat supply system.